Peak hour in the bush: Linear anthropogenic clearings funnel predator and prey species - Dawson, S.; Adams, P.; Moseby, K.; Waddington, K.; Kobryn, H.; Bateman, Bill; Fleming, P. (Blackwell Publishing Asia, 2017)
© 2017 Ecological Society of Australia. Linear clearings, such as roads and tracks, are an obvious anthropogenic feature in many remote environments, even where infrastructure is sparse. Predator species have been shown to prefer moving down linear clearings, and therefore, clearings could increase predation risk for other species. We investigated whether tracks cleared for seismic surveys are preferentially used by predators and herbivores in a landscape inhabited by bilbies (Macrotis lagotis), a vulnerable species of conservation concern. We used a paired camera trap array to investigate the use of cleared seismic lines at four time points after clearing (1 month, 3 months, 7 months, 48 months) by six mammal species. Bilbies, cattle (Bos indicus/B. taurus), dingoes (Canis familiaris), feral cats (Felis catus) and agile wallabies (Macropus agilis) preferred to use seismic lines compared with adjacent undisturbed vegetation for almost all surveys, while spectacled hare wallabies (Lagorchestes conspicillatus) avoided them. Bilbies and agile wallabies showed similar temporal activity patterns on and off seismic lines but feral cats, dingoes and cattle used seismic lines at different times of day to control areas. We also investigated microhabitat selection by spool tracking individual bilbies. Bilbies selected a route through vegetation that was more open than surrounding vegetation. While spatial and temporal funnelling of bilbies and their predators (especially cats) may increase the frequency of encounter between the two, it is important to note that bilbies were active at significantly different times to predators both on and off seismic lines. The identified selection for seismic lines, and changes in spatial and temporal overlap between species, can be used to develop effective management strategies, to minimize potential impacts on native species.